2020
DOI: 10.3390/ani10071234
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heat Stress Induces the Differential Expression of Heat Shock Proteins in Different Sections of the Small Intestine of Chickens Based on Exposure Duration

Abstract: In this study, we examined the protein and gene expression of heat shock proteins (HSPs) in different sections of the small intestine of chickens. In total, 300 one-day-old Ross 308 broiler chicks were randomly allocated to the control and treatment groups. The treatment group was divided into four subgroups, according to the duration of acute heat exposure (3, 6, 12, and 24 h). The influence of heat stress on the protein and gene expression of HSP70, HSP60, and HSP47 in different sections of the small intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Liu et al [ 46 ] reported that chronic cyclic heat stress-induced intestinal damage and altered cecal microflora profile via oxidative stress induction. Acute heat stress was also reported to cause serious damages in chickens’ small intestine and liver [ 47 ]. Adding Spirulina to heat-stressed chickens significantly improved growth performance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 46 ] reported that chronic cyclic heat stress-induced intestinal damage and altered cecal microflora profile via oxidative stress induction. Acute heat stress was also reported to cause serious damages in chickens’ small intestine and liver [ 47 ]. Adding Spirulina to heat-stressed chickens significantly improved growth performance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HSP70 is known as a cellular thermometer [ 43 ]. As heat stress increased, the gene expression of HSP70 was up-regulated to protect the cell damages by triggering protein expression [ 6 , 44 ]. The HSPs isoforms response differently to heat stress [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins are also upregulated during heat stress periods. They stimulate cytoprotection and induce heat tolerance in the cells of various organs and tissues by repairing damaged or misfolded proteins and promoting cell survival ( Hasan Siddiqui et al., 2020 ). It would be interesting to elucidate whether supplementation of Met is also able to influence the expression of heat shock proteins in tissues broilers of during exposure to heat stress.…”
Section: Discussionmentioning
confidence: 99%